A Symbolic Message About the War in the Photos of Red Army Photo Correspondent Emmanuil Evzerikhin from 1945 - Gliniecki, Tomasz (Faces of War, 2024)
War photography is rarely treated by researchers of the past as a separate historical source. It rarely becomes a subject of in-depth research or separate academic studies. Even if its documentary value is noted, it is considered in the convention of image carriers rather than separate material for analysis. Meanwhile, the source knowledge about the war contained in the photographs allows military historians specialising in decoding it to use it broadly for cognitive purposes. In this paper, the author presents and discusses the symbolic narrative elements contained in the photographs taken in the final stages of World War II by Red Army photo correspondent, Captain Emmanuil Noevich Evzerikhin (Эммануил Ноевич Евзерихин). At the same time, the paper shows that the photographer’s individual work was harnessed to execute tasks of the military propaganda services.